1990
DOI: 10.1172/jci114852
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human bone-related proteins in the hematopoietic microenvironment.

Abstract: Given the intimate relationship between bone and bone marrow, we hypothesized that the human bone marrow may function as a source (or reservoir) of bone-forming progenitor cells. We observed a population of cells within the bone marrow which produce bone-specific or bone-related proteins. The production of these proteins was developmentally regulated in human long-term bone marrow cell cultures; the bone proteinproducing cells (BPPC) are observed under serum-free, shortterm culture conditions, respond to bone-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 41 publications
5
70
1
Order By: Relevance
“…Moreover, molecular analysis demonstrated a common retroviral integration site in clonogenic hematopoietic cells and osteoprogenitors from each of seven animals studied, establishing a shared clonal origin for these cell types. These findings thus lent considerable credence to the previous work of Long et al [3,4] and established that, at least in the experimental paradigm used by Dominici and colleagues [9], non-adherent bone marrow cells have a >10-fold more robust bone-repopulating activity than do adherent bone marrow stromal cells. Moreover, the findings were also consistent with previous work by Olmsted-Davis et al [10] suggesting the presence of a unique progenitor cell with both hematopoietic and osteoblastic differentiation potential in the non-adherent subset of bone marrow cells.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…Moreover, molecular analysis demonstrated a common retroviral integration site in clonogenic hematopoietic cells and osteoprogenitors from each of seven animals studied, establishing a shared clonal origin for these cell types. These findings thus lent considerable credence to the previous work of Long et al [3,4] and established that, at least in the experimental paradigm used by Dominici and colleagues [9], non-adherent bone marrow cells have a >10-fold more robust bone-repopulating activity than do adherent bone marrow stromal cells. Moreover, the findings were also consistent with previous work by Olmsted-Davis et al [10] suggesting the presence of a unique progenitor cell with both hematopoietic and osteoblastic differentiation potential in the non-adherent subset of bone marrow cells.…”
Section: Introductionsupporting
confidence: 77%
“…We found that OCN pos cells isolated using either the antibody we used in our previous work (SC V-19) [14] or the antibody used by Long and colleagues (HT AON-5031) [3,4] identified very similar populations of cells, at least as assessed by flow cytometry and confocal microscopy. While additional studies need to be done further characterizing the cells isolated with the two antibodies, these data do provide some reassurance that the cells identified in our previous work using the SC V-19 antibody are not some type of spurious population staining only with this particular antibody.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations